Protective Efficacy and Long-Term Immunogenicity in Cynomolgus Macaques by Ebola Virus Glycoprotein Synthetic DNA Vaccines. (10th October 2018) - Patel, Ami; Reuschel, Emma L; Kraynyak, Kimberly A; Racine, Trina; Park, Daniel H; Scott, Veronica L; Audet, Jonathan; Amante, Dinah; Wise, Megan C; Keaton, Amelia A; Wong, Gary; Villarreal, Daniel O; et al.
Abstract : Intradermal delivery of an EBOV-GP DNA vaccine is dose sparing and protective against lethal challenge in macaques and induces durable immune responses. This vaccine is a safe nonlive, temperature stable, serological independent alternative approach for protection of vulnerable populations among others. Abstract: Background: There remains an important need for prophylactic anti-Ebola virus vaccine candidates that elicit long-lasting immune responses and can be delivered to vulnerable populations that are unable to receive live-attenuated or viral vector vaccines. Methods: We designed novel synthetic anti-Ebola virus glycoprotein (EBOV-GP) DNA vaccines as a strategy to expand protective breadth against diverse EBOV strains and evaluated the impact of vaccine dosing and route of administration on protection against lethal EBOV-Makona challenge in cynomolgus macaques. Long-term immunogenicity was monitored in nonhuman primates for >1 year, followed by a 12-month boost. Results: Multiple-injection regimens of the EBOV-GP DNA vaccine, delivered by intramuscular administration followed by electroporation, were 100% protective against lethal EBOV-Makona challenge. Impressively, 2 injections of a simple, more tolerable, and dose-sparing intradermal administration followed by electroporation generated strong immunogenicity and was 100% protective against lethal challenge. In parallel, we observed that EBOV-GP DNA vaccination induced long-term immune responses in macaques that were detectable for at least 1 year after final vaccination and generated a strong recall response after the final boost. Conclusions: These data support that this simple intradermal-administered, serology-independent approach is likely important for additional study towards the goal of induction of anti-EBOV immunity in multiple at-risk populations.